Six month-follow up of laparoscopic sleeve gastrectomy - Behrouz Keleidari (Advanced Biomedical Research, 2016)
Background: The rising prevalence of obesity in today populations has led obese individuals to seek medical interventions. Aside from special diets, routine exercise and in some cases, medical treatment, most of the obese patients, favoring those with morbid or super obesity can benefit from bariatric surgery to lose weight. Laparoscopic sleeve gastrectomy (LSG) is relatively new method to limit the compliance of stomach. The consequent quick satiety during each meal results in gradual weight loss in patients. We investigated the efficacy and safety of this method among a group of our patients. Materials and Methods: This cross-sectional study was conducted in Isfahan, Iran, from January 2012 to January 2013. Thirty-five cases of obesity that had undergone LSG were enrolled and their baseline data of weight, body mass index (BMI), blood sugar, lipid profile, liver function indexes and blood pressure were collected. The patients were followed up for 6 months. The 6-month results were analyzed. Results: There was significant reduction in BMI, weight, blood sugar, blood pressure, liver enzymes and lipid profile components (P < 0.05), except for alkaline phosphatase (ALP) (P = 0.3). The average of excess weight loss percentage after 6 months was 69.2 ± 20.9%. No mortality occurred. Two of the patients had micro anastomotic leaks that were treated with nonoperative management. A case of gross leakage was treated with tube jejunostomy. Conclusion: Our study confirmed the efficacy and safety of LSG as a single surgical intervention for body weight reduction in morbidly and super obese patients.